Antimicrobial and wear performance of Cu-Zr-Al metallic glass composites. (5th February 2017) - Villapún, Victor M.; Zhang, H.; Howden, C.; Chow, L. Cheung; Esat, F.; Pérez, P.; Sort, J.; Bull, S.; Stach, J.; González, S.
Abstract: The antimicrobial and wear behaviour of metallic glass composites corresponding to the Cu50 + x (Zr44 Al6 )50 − x system with x = (0, 3 and 6) has been studied. The three compositions consist of crystalline phases embedded in an amorphous matrix and they exhibit crystallinity increase with increasing Cu content, i.e., decrease of the glass-forming ability. The wear resistance also increases with the addition of Cu as indirectly assessed from H/Er and H 3 /Er 2 parameters obtained from nanoindentation tests. These results are in agreement with scratch tests since for the alloy with highest Cu content, i.e., Cu56 Zr38.7 Al5.3, reveals a crack increase, lower pile-up, prone adhesion wear in dry sliding and higher scratch groove volume to pile-up volume. Samples with higher Cu content revealed higher hydrophilicity. Time-kill studies revealed higher reduction in colony-forming units for E. coli (gram-negative) and B. subtilis (gram-positive) after 60 min of contact time for the Cu56 Zr38.7 Al5.3 alloy and all the samples achieved a complete elimination of bacteria in 250 min. Graphical abstract: Highlights: The wear resistance increases with the addition of copper from 50 to 56 at.%. The contact angle values decrease with increasing Cu content. Maximum antimicrobial behaviour and wear resistance is attained by the Cu56 Zr38.7 Al5.3 composition.